Photoacoustic signal amplification through plasmonic nanoparticle aggregation - Bayer, Carolyn L. (Society of Photo-Optical Instrumentation Engineers, 2013)
Photoacoustic imaging, using targeted plasmonic metallic nanoparticles, is a promising noninvasive molecular imaging method. Analysis of the photoacoustic signal generated by plasmonic metallic nanoparticles is complex because of the dependence upon physical properties of both the nanoparticle and the surrounding environment. We studied the effect of the aggregation of gold nanoparticles on the photoacoustic signal amplitude. We found that the photoacoustic signal from aggregated silica-coated gold nanoparticles is greatly enhanced in comparison to disperse silica-coated gold nanoparticles. Because cellular uptake and endocytosis of nanoparticles results in their aggregation, these results have important implications for the application of plasmonic metallic nanoparticles towards quantitative molecular imaging.